Ninjinyoeito improves social behavior disorder in neuropeptide Y deficient zebrafish - Kawabe, Momoko; Nishida, Takumi; Horita, Chihoko; Ikeda, Asami; Takahashi, Ryuji; Inui, Akio; Shiozaki, Kazuhiro (Frontiers in Pharmacology, 2022)
Sociability is an essential component of the linkage structure in human and other vertebrate communication. Low sociability is defined as a poor social approach, including social withdrawal and apathy, and is implicated in a variety of psychiatric disorders. Ninjinyoeito (NYT), a traditional Japanese herbal medicine, has been used in the medical field. This study aimed to determine the effect of NYT on low sociality in NPY-KO zebrafish. NPY-KO zebrafish were fed a 3% NYT-supplemented diet for four days and subjected to behavioral tests. In the mirror test, NPY-KO zebrafish fed a control diet showed avoidance behavior toward their mirror counterparts. In contrast, the treatment of NPY-KO zebrafish with NYT significantly increased their interaction with their counterparts in the mirror. In addition, a 3-chambers test was conducted to confirm the effect of NYT on the low sociality of NPY-KO zebrafish. NPY-KO zebrafish fed the control diet showed less interaction with fish chambers, while NYT treatment increased the interaction. Phosphorylation of ERK, a marker of neuronal activity, was significantly reduced in the whole brain of NYT-fed NPY-KO zebrafish, compared to the control diet. NYT treatment significantly suppressed hypothalamic-pituitary-adrenal-related genes (gr, pomc, and crh) and sympathetic-adrenal-medullary-related genes (th1, th2, and cck) in NPY-KO zebrafish. NYT administration significantly reduced mRNA levels of gad1b compared to the control diet, suggesting the involvement of GABAergic neurons in NYT-induced improvement of low sociability. Furthermore. the expression of CREB was suppressed when NPY-KO zebrafish were fed NYT. Next, we attempted to identify the effective herb responsible for the NYT-induced improvement of low sociability. NPY-KO zebrafish were fed an experimental diet containing the target herb for four days, and its effect on sociability was evaluated using the 3-chambers test. Results showed that Cinnamon Bark and Polygala Root treatments significantly increased time spent in the fish tank area compared to the control diet, while the other 10 herbs did not. We confirmed that these two herbs suppressed the activity of HPA-, SAM-, and GABAergic neurons, as well as NYT-treated zebrafish, accompanied by down-regulation of CREB signaling. This study suggests the potential use of NYT as a drug for sociability disorders.